Material hardness at strain rates beyond 106 s−1 via high velocity microparticle impact indentation. (1st March 2020) - Hassani, Mostafa; Veysset, David; Nelson, Keith A.; Schuh, Christopher A.
Abstract: Despite advances in mechanical testing at small scales and testing at high strain rates, studies of mechanical behavior of materials remain largely qualitative in the regimes where these two conditions overlap. Here, we present an approach based on microparticle impact indentation to determine material hardness at micron scales and at high strain rates. We employ laser ablation to impact ceramic alumina microparticles (as indenter) onto two model materials, namely copper and iron. We use real time measurements of impact and rebound velocities together with post-impact measurements of indentation volume to determine material hardness at strain rates beyond 10 6  s −1 . Graphical abstrcat: Image, graphical abstract